2016
DOI: 10.1007/s13361-016-1342-z
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Protonated N-(3-Aminophenyl)Benzamide and Its Derivatives in Gas Phase

Abstract: Abstract. An ion of m/z 110.06036 (ion formula [C 6 H 8 . Theoretical calculations using Density Functional Theory (DFT) at B3LYP/6-31 g(d) level suggest that an ion-neutral complex containing a water molecule and a nitrilium ion was formed via a transition state (TS-1), followed by the water molecule migrating to the anilide ring, eventually leading to the formation of the rearranged ion of m/z 110. The rearrangement can be generalized to other protonated amide compounds with electron-donating groups at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…In some cases, even the structural class of the molecule was different from what was claimed on the bottle. A recent paper describing a mislabeled synthetic compound shows nicely how mass spectrometry can be used to detect such a problem (Zu et al, 2016). Thus, it is possible that some of the reference standards used to produce spectra of abietic/neoabietic acid were mislabeled.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, even the structural class of the molecule was different from what was claimed on the bottle. A recent paper describing a mislabeled synthetic compound shows nicely how mass spectrometry can be used to detect such a problem (Zu et al, 2016). Thus, it is possible that some of the reference standards used to produce spectra of abietic/neoabietic acid were mislabeled.…”
Section: Resultsmentioning
confidence: 99%
“…Although this pathway was minor (~ 2% of the base peak) it is mechanistically interesting considering that loss of water in tandem mass spectra is typically associated with the presence of a hydroxyl group. Loss of water from N ‐(3‐aminophenyl) benzamide was reported recently by Zu et al and has been shown to involve a water‐nitrilium ion complex . While this mechanism might be operational for our compounds, we propose another mechanism that involves electrophilic attack of the protonated amideonto the aromatic ring as shown in Scheme .…”
Section: Resultsmentioning
confidence: 54%
“…Jiang and co-workers reported a novel oxygen transfer pathway in the dissociation of protonated N -phenyl p -toluenesulfonamides, whereby an oxygen atom of sulfonyl group is transferred to the ortho, meta, or para position of the aniline ring in the CID process. Zu reported an unprecedented reaction via N–O exchange in the CID experiments of protonated N -(3-aminophenyl)­benzamide. The carbonyl oxygen was transferred to the aniline ring by a water molecule migration rearrangement.…”
Section: Introductionmentioning
confidence: 99%